Swedish police officers' strategies when interviewing suspects who decline to answer questions. (28th April 2022) - Magnusson, Mikaela; Ernberg, Emelie; Granhag, Pär Anders; Nyström, Lina; Luke, Timothy J.
Abstract: Purpose: Research‐based interviewing techniques typically rely upon suspects being, at least partially, responsive and engaged in the conversation. To date, the scientific literature is more limited regarding situations where suspects exercise their legal right to silence. The present study aimed to examine Swedish police officers' self‐reported strategies when interviewing suspects who decline to answer questions. Methods: A total of 289 police officers responded to a national survey that included questions about handling silence. The participants worked with a wide range of criminal cases, including financial crimes, fraud, violent offences, domestic abuse, volume crime and traffic violations. We used content analysis to examine their written responses to the open‐ended question : 'What, if any, strategies do you use when interviewing suspects who speak very little or not at all?' Results: Four main categories were identified relating to (1) question strategies (e.g. asking the questions anyway, using silence), (2) information strategies (e.g. emphasizing the benefits of cooperating and informing about their legal right to silence), (3) supportive strategies (e.g. being friendly and asking about reasons for silence) and (4) procedural strategies (e.g. changing interviewers and conducting multiple interviews). Practitioners working with violent crimes reported meeting silent suspects more frequently compared with practitioners working with other criminal offences. Conclusions: The results provide an initial exploration into the various strategies used by police interviewers when questioning suspects who decline to answer questions. Further research is necessary for understanding and evaluating the ethics and effectiveness of such strategies.